2021
DOI: 10.1088/2040-8986/ac160d
|View full text |Cite
|
Sign up to set email alerts
|

The hollow Gaussian beam propagation on curved surface based on matrix optics method

Abstract: In this paper, ABCD matrix is introduced to study the paraxial transmission of light on a constant gaussian curvature surface (CGCS), which is the first time to our knowledge. It is also proved that the curved surface can be used as the implementation of fractional Fourier transform, we further generalize that we can obtain the transfer matrix of an arbitrary surface with gently varying curvature by matrix optics. As a beam propagation example, based on the Collins integral, an analytical propagation formula f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(64 reference statements)
2
5
0
Order By: Relevance
“…where ρ = ρ b − ρ a . It is worth noting that this analytic solution is consistent with that obtained by the optical matrix and Collins formula in reference [26]. Equation ( 2) is a linear differential equation whose solutions satisfy the linear superposition property, thus by assuming eigen-solutions u n (h, ρ), a special set of solutions, we can separated it into the following form:…”
Section: Path Integral Methods and Quantized Momentumsupporting
confidence: 80%
See 2 more Smart Citations
“…where ρ = ρ b − ρ a . It is worth noting that this analytic solution is consistent with that obtained by the optical matrix and Collins formula in reference [26]. Equation ( 2) is a linear differential equation whose solutions satisfy the linear superposition property, thus by assuming eigen-solutions u n (h, ρ), a special set of solutions, we can separated it into the following form:…”
Section: Path Integral Methods and Quantized Momentumsupporting
confidence: 80%
“…where η σ p h = u σ e −ip h h dh is the Fourier transform of u σ . According to equation (12), it is found that the transmission of the light beam along axis can be regarded as the rotation in the position-momentum (h − p h ) space, which coincides with our previous discussion that CGCS can be regarded as a fractional Fourier transform system [26,27]. Furthermore, the coordinate uncertainty (spot size) and momentum uncertainty can be obtained by the second moment:…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The 2D surface light transmission simulation of the general relativistic effect is largely based on the related theories of the 3+1 membrane paradigm [9] and embedding diagrams. In recent years, great progress has been made in theory [10][11][12][13][14][15] and…”
Section: The "Quantized" Momentum On Cgcss and The Hawking Temperaturementioning
confidence: 99%
“…[8] Unlike other fields that require relativistic laboratory tests of strong gravitational fields, optical studies can be carried out under a 2D analog.The 2D surface light transmission simulation of the general relativistic effect is largely based on the related theories of the 3+1 membrane paradigm [9] and embedding diagrams. In recent years, great progress has been made in theory [10][11][12][13][14][15] and…”
mentioning
confidence: 99%